2021
DOI: 10.1038/s41598-021-01689-2
|View full text |Cite
|
Sign up to set email alerts
|

A selectable all-in-one CRISPR prime editing piggyBac transposon allows for highly efficient gene editing in human cell lines

Abstract: CRISPR prime-editors are emergent tools for genome editing and offer a versatile alternative approach to HDR-based genome engineering or DNA base-editors. However, sufficient prime-editor expression levels and availability of optimized transfection protocols may affect editing efficiencies, especially in hard-to-transfect cells like hiPSC. Here, we show that piggyBac prime-editing (PB-PE) allows for sustained expression of prime-editors. We demonstrate proof-of-concept for PB-PE in a newly designed lentiviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Some prime editing applications, such as pooled screening, require stable cellular expression of PE from a genomically integrated cassette. PiggyBac transposase and lentiviruses can stochastically insert DNA encoding PEs and pegRNAs into the genome and mediate high editing efficiencies in human cell lines, induced pluripotent stem cells (iPSCs) and mouse cortical neurons 52,55,[109][110][111] . Similarly, human iPSC lines have been generated with inducible PE2 at the AAVS1 safe harbour locus by HDR-mediated integration 82,112,113 .…”
Section: Dna Transfection and Viral Deliverymentioning
confidence: 99%
“…Some prime editing applications, such as pooled screening, require stable cellular expression of PE from a genomically integrated cassette. PiggyBac transposase and lentiviruses can stochastically insert DNA encoding PEs and pegRNAs into the genome and mediate high editing efficiencies in human cell lines, induced pluripotent stem cells (iPSCs) and mouse cortical neurons 52,55,[109][110][111] . Similarly, human iPSC lines have been generated with inducible PE2 at the AAVS1 safe harbour locus by HDR-mediated integration 82,112,113 .…”
Section: Dna Transfection and Viral Deliverymentioning
confidence: 99%
“…remain integrated in the genome; thus, this system is not scarless. Eggenschwiler et al presented a similar system, but with the ability to excise the prime editing components following the editing step using the piggyBac system for scarless editing [ 45 ].…”
Section: Strategies To Increase Hdr-dependent Crispr-cas9 Mediated Ge...mentioning
confidence: 99%
“…For example, Bharucha et al [23] developed a doxycycline-inducible-PE2 expressing iPSC line that provides a fast and efficient approach. Similarly, the PE construct was integrated into the genome via a piggyBac transposon, enabling sustained expression of the protein and efficient edit in iPSC cells [24]. Finally, Habib et al [25] created a drug-inducible PE2-expressing human embryonic stem cell (hESC) line to introduce small indels and all base substitutions and showed that long-term overexpression of PE2 did not generate significant frequencies of genome-wide SNVs or indels.…”
Section: Advantages Of Prime Editingmentioning
confidence: 99%